#TITLE_ALTERNATIVE# - AGUSTINUS SUSANTO (NIM 10105011), ERIK
Every financial assets in the form of stocks will encounter the risk of decreasing asset value in a period of time. To keep the asset value not decreased, the investors can implement hedging strategy. One way of hedging is buying European put option, which means buying the right to sell assets in the form of stocks in certain price known as strike price. But using this put option does not mean that the risk can be vanished since for buying an option need a cost. That is way conscientious decision is extremely needed in buying this put option. In this final project, we measure the portfolio risk by Value at Risk (VaR), which is the maximum loss predicted happens during the period of investment time with a certain confidence level. With fixed hedging cost, investor can determine strike price which minimize VaR. Determining strike price which minimizing VaR for in-the-money case has been discussed in Ahn paper [1]. This final project try to generalize the research, where we consider both case in-the-money and out-the-money. The optimal strike price evaluated in two approaches, using distribution of asset future value and Monte Carlo simulation. In the first approach, the optimal strike price can be written as optimization problem with implicit objective function. Genetic Algorithm used to solve this optimization problem. Both approaches give a relatively similar optimal strike price.